2013
DOI: 10.4244/eijv9i3a62
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of polymer response to delivery balloon expansion of drug-eluting stents versus bare metal stents

Abstract: Balloon expansion of first- and second-generation DES disturbs the polymer surface and can cause detachment of microparticles; each is functionally related to the specific polymer but not to expansion condition. Disturbance "roughness" and detached microparticles may contribute to DES limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…An initial systematic classification and quantification of coating irregularities on the surface of various types of DES reported in 2009 showed that the incidence and size of various coating irregularities differed widely among different types of DES 11 . The present carefully executed study of Denardo and co-workers builds further on the available literature and confirms that important qualitative and quantitative differences in surface coating exist among approved DES platforms that are in routine clinical use 6 . Earlier research on expanded (and post-dilated) DES demonstrated loosely attached polymer particles with a very wide range of size, e.g., approximately 30 µm on a durable polymer-based DES coating ( Figure 1C) versus up to 300 µm on a biodegradable polymer-based DES coating ( Figure 1D) 10,11 .…”
Section: Des Coating Irregularities and Fragments Reported In The Litsupporting
confidence: 72%
See 2 more Smart Citations
“…An initial systematic classification and quantification of coating irregularities on the surface of various types of DES reported in 2009 showed that the incidence and size of various coating irregularities differed widely among different types of DES 11 . The present carefully executed study of Denardo and co-workers builds further on the available literature and confirms that important qualitative and quantitative differences in surface coating exist among approved DES platforms that are in routine clinical use 6 . Earlier research on expanded (and post-dilated) DES demonstrated loosely attached polymer particles with a very wide range of size, e.g., approximately 30 µm on a durable polymer-based DES coating ( Figure 1C) versus up to 300 µm on a biodegradable polymer-based DES coating ( Figure 1D) 10,11 .…”
Section: Des Coating Irregularities and Fragments Reported In The Litsupporting
confidence: 72%
“…While polymer coatings have a central role in ensuring the antirestenotic efficacy of DES devices -and may even have an acute protective role in reducing thrombogenicity -these advantages occur at the collateral cost of a significant delay in arterial healing in comparison with uncoated stents, and an associated spectrum of clinicopathological events including late thrombotic stent occlusion. The present report of Denardo et al 6 sheds further light on the issue of balloon expansion-induced polymer disruption and microparticle liberation, an effect that appeared to vary among DES types studied. Although the clinical relevance of these findings remains to be fully elucidated, the potential relevance is such that in our opinion detailed bench evaluation of polymer coating integrity should be incorporated into European regulatory body approval processes, as is the case in the United States.…”
Section: Perspectivesupporting
confidence: 58%
See 1 more Smart Citation
“…Human autopsy studies have identified the polymer coating of the stent's metal struts as a possible trigger for chronic local inflammatory response within the vessel wall [8,9]. Moreover, ex-vivo scanning electron microscopy examinations of DESs before and after balloon expansion, demonstrated inhomogeneous distribution and poor integrity of the polymer coating, in all commercially available DESs examined [10,11].These irregularities, cracks and fractures of the polymer's surface are thought to trigger local inflammatory reaction in the vessel wall, leading to increased risk of late stent thrombosis and in-stent restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In scanning electron microscopy studies, cracks and inhomogeneous distribution of coating have been observed on all DES types assessed. 14,15 Such occurrences can promote platelet aggregation, stent thrombosis and, in individuals with diabetes, trigger an inflammatory response within the vessel wall, potentially accelerating progression of atherosclerosis and risk of restenosis. 16…”
mentioning
confidence: 99%